TRANSFORMASI KELEMBAGAAN GUNA MEMPERKUAT EKONOMI RAKYAT DI PEDESAAN: SUATU KAJIAN ATAS KASUS DI KABUPATEN TABANAN, BALI - -, SAPTANA; PRANADJI, TRI; -, SYAHYUTI; ELIZABETH, ROOSGANDA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 1 Februari 2004, 2012)
Weak national economy is resulted from powerless rural economy, and the main cause is fragile supporting institution. If rural economy is not transformed to strong one, the future of rural economy will be insignificant. There are three pillars in rural community, namely local or traditional communal institution, private sector, and public sector. The research aimed (1) to study characteristics and performance of traditional institution historically, (2) to evaluate programs related with public economy development in rural areas, (3) to assess the structure of three pillars institution, (4) to find critical points of traditional institutional transform to strengthen rural economy along with globalization and regional autonomy, and (5) to formulate traditional institution transform model along with globalization and regional autonomy. The Steps of Rural Economic Institutional Tranformation i.e. : communal society era, destroyed communal society era, and new communal era. Some Types of Institutional Tranformation. This research find that the institutional tranformation still in transition stage. There are some type of traditional instiutional transformation, those are: replaced structure with new structure, adding structure, new missions and objectives, and new norm system. The Mode of Institutional Transformation. As explained in think frame, instituional change is depend on three of power, i.e. government, market, and community. This research also find that community power in market institution have replaced the government support, i.e. in cooperatives organization (KUD). Deminishing of the government support gave positive impact to KUD, where they are more creative and autonom in planning and action program. Succesfull of development LPD due to the local leadership support and community participation. This is fenomenon where the community principle use in market isntitution, especially in credit program. Institutional transformation mode have five aspects, those are agricultural instituional and organization, leadership, human resources, the value system, and socio culture.
Keywords: Transformation, Institutional, Strengthened, Rural Economy